The Influence of Organizational Climate and Leader Member Exchange on Organizational Citizenship Behavior (OCB) of Civil Servants at the Food Security, Food Crops, Horticulture and Fisheries Office of Sanggau Regency - Yolanda Ulandari; Devi Yasmin (Universitas KH. Abdul Chalim Mojokerto, 2025)
The success of an organization in achieving its goals is highly dependent on the quality of its human resources, where employees act as the main asset. One important factor in employee management is the organizational climate and the quality of the relationship between superiors and subordinates known as Leader-Member Exchange (LMX). This study aims to determine the effect of organizational climate and LMX on the Organizational Citizenship Behavior (OCB) of Civil Servants at the Food Security, Food Crops, Horticulture, and Fisheries Service (DKPTPHP) of Sanggau Regency. This study uses a quantitative approach with an associative research type, which aims to determine the relationship between two or more variables. The data analysis techniques used are multiple linear regression analysis, F test, and t test. The results of the study indicate that simultaneously, organizational climate and LMX have a significant effect on OCB with a correlation coefficient (R) of 0.570 and a determination coefficient (R²) of 32.50%. However, partially, only the LMX variable has a significant effect on OCB, while organizational climate does not have a significant effect. Thus, a quality superior-subordinate relationship plays an important role in increasing employee voluntary work behavior that goes beyond their formal duties. This finding can be a reference for organizations to pay more attention to the interpersonal relationship aspect in an effort to improve employee performance and loyalty. Check how many words there are.